Puddin' : Dumplin' #2 - Murphy, Julie, 1985- (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2018)
When circumstances put Millie Michalchuk and Callie Reyes together over the course of a semester, the girls realize they have more in common than they ever imagined.
Keywords: Obesity -- Fiction; Female friendship -- Fiction; Overweight persons -- Fiction; Female friendship -- Fiction; Texas -- Fiction; Texas -- Fiction